Pediatric duodenal stenosis caused by posttraumatic mesenteric hematoma managed with a double elementary diet tube - Hirotaka Shibuya; Keita Sato; Natsuki Hashiba; Yosuke Yamauchi; Yoshihisa Tamura; Shinya Sugimoto; Koji Takahashi (Trauma Case Reports)
A 6-year-old male child was admitted to the hospital because of abdominal trauma and acute stomach pain. Computed tomography scan revealed a jejunal mesenteric hematoma and an enhanced intestinal wall compressed by the hematoma. The patient presented with vomiting 10 days after the injury. He underwent upper endoscopy under tracheal intubation and general anesthesia 12 days after the injury. A double elementary diet tube was inserted endoscopically with the tip placed in the jejunum beyond the stenosis and the decompressed portion of the stomach. Stenosis was improving, and the patient was discharged on the 27th day after the injury. In conclusion, a double elementary diet tube can be effective for treating posttraumatic duodenal stenosis in pediatric patients.